What determines Bank Profitability in the United States in a post crisis environment? - Avgush, Lior (2015)
This study explores the effect of a post crisis environment on the technical efficiencies and profitability determinants of the United States banking sector. The analysis is broken down into two stages. The first stage utilizes Stochastic Frontier Analysis (SFA) to estimate the technical efficiency scores for individual banks in the sample, while the second stage looks into the determinants of bank profitability, including the efficiency estimates from the analysis conducted in the first stage of this study. Only strictly commercial banks deemed systematically important by the United States Treasury were chosen for this study. The chosen 19 banks were analyzed over a five year period from 2009 to 2014. The analysis highlights links between bank behavior and post crisis regulation, such as drops in efficiency corresponding to higher capital requirements in result of Basel III being phased in. Profitability determinants are also analyzed and interpreted separately to uncover revenue drivers in a post crisis environment.